Tracking biochemical changes correlated with ultra-weak photon emission using metabolomics - Burgos, Rosilene Cristina Rossetto; Červinková, Kateřina; van der Laan, Tom; Ramautar, Rawi; van Wijk, Eduard P A; Cifra, Michal; Koval, Slavik; Berger, Ruud; Hankemeier, Thomas; van der Greef, Jan (Journal of photochemistry and photobiology. B, Biology, 2016)
Ultra-weak photon emission (UPE) is light emitted spontaneously by biological systems without the use of specific luminescent complexes. UPE is emitted in the near-UV/UV-Vis/near-IR spectra during oxidative metabolic reactions; however, the specific pathways involved in UPE remain poorly understood. Here, we used HL-60 cells, a human promyelocytic cell line that is often used to study respiratory burst, as a model system to measure UPE kinetics together with metabolic changes. HL-60 cells were differentiated into neutrophil-like cells by culturing in all-trans-retinoic acid for 7days. We then used a targeted metabolomics approach with capillary electrophoresis-mass spectrometry to profile intracellular metabolites in HL-60 cells and to investigate the biochemical changes based on the measured UPE profile. Our analysis revealed that the levels of specific metabolites, including putrescine, creatine, β-alanine, methionine, hydroxyproline, serine, and S-adenosylmethionine, were significantly altered in HL-60 cells after inducing respiratory burst. A comparison with recorded UPE data revealed that the changes in putrescine, glutathione, sarcosine, creatine, β-alanine, methionine, and hydroxyproline levels were inversely correlated with the change in UPE intensity. These results suggest that these metabolic pathways, particular the methionine pathway, may play a role in the observed changes in UPE in HL-60 cells and therefore demonstrate the potential for using UPE to monitor metabolic changes.
Keywords: tetradekanoylforbolacetát; HL-60 cells; Tetradecanoylphorbol Acetate; Metabolomics; HL-60 buňky; Cell Respiration; metabolomika; buněčné dýchání; buněčná diferenciace; Ultra-weak photon emission; neutrofily; Photons; lidé; HL-60 Cells; Capillary electrophoresis-mass spectrometry; Humans; Neutrophils; Cell Differentiation; fotony